TRAINING OF TRAINERS AS A TOOL FOR SOCIAL PREVENTION OF HUMAN TRAFFICKING AMONG ADOLESCENTS - Zolotarenko, Viktor (Theoretical and Methodical Problems of Children and Youth Education, 2022)
The article outlines the specifics of the implementation of social technology training of trainers in social work with adolescents for social prevention of human trafficking and researched the impact of implementation on the awareness of adolescents about human trafficking and prevention of human trafficking. The purpose of the article is to present the results of research into the social technology of training of trainers in social work with adolescents for social prevention of human trafficking. The following task is singled out: to give a substantive description of social technology for social work with adolescents and to investigate the implementation of social technology with adolescents and reveal its results. During the research, the following methods were used: theoretical – analysis and synthesis to compare the views of scientists used in training methods and to compare the ways of providing social and preventive influence; empirical – questionnaires for collecting research results. The study is based on the practice of conducting three trainings of trainers for combating human trafficking among adolescents in the project “Increasing the awareness of various populations of the Dnipropetrovsk oblast regarding safe migration and employment”. The participants in trainings of trainers were 48 students aged 14-16 of Dnipro I-II accreditation levels. According to the results of the implementation of trainings of trainers, adolescents’ awareness of human trafficking and prevention of human trafficking has increased. It is shown the effectiveness of this social technology. The results of the research can be used in the further theoretical development of the topic of combating human trafficking and in the practical activities of social work specialists.